A Model of Catalytic Cracking: Catalyst Deactivation Induced by Feedstock and Process Variables; Catalysts; Vol. 12, iss. 1 - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Mezhova M. Yu. Mariya Yurjevna (2022, 2022)
Title screen